2015
DOI: 10.1016/j.medici.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of exploratory factor analysis to ascertain the correlation between the activities of rheumatoid arthritis and infection by human parvovirus B19

Abstract: Using EFA and DAS28, a correlation between the clinical activity of RA and B19 infection was confirmed. These data suggest that EFA is applicable for medico-biological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…they have persistent infection in the active phase. Our data coincide with previously published data, in showing that the prevalence of B19V DNA in serum, plasma or peripheral blood cells was significantly higher in patients with RA than in controls (Caliskan et al , 2005; Chen et al , 2006; Kozireva et al , 2008; Tzang et al , 2009b) and that RA activity was higher in patients with latent/persistent B19V infection (Kakurina et al , 2015). However, some authors concluded that B19V is not involved in the aetiopathogenesis of RA (Kerr et al , 1995; Nikkari et al , 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…they have persistent infection in the active phase. Our data coincide with previously published data, in showing that the prevalence of B19V DNA in serum, plasma or peripheral blood cells was significantly higher in patients with RA than in controls (Caliskan et al , 2005; Chen et al , 2006; Kozireva et al , 2008; Tzang et al , 2009b) and that RA activity was higher in patients with latent/persistent B19V infection (Kakurina et al , 2015). However, some authors concluded that B19V is not involved in the aetiopathogenesis of RA (Kerr et al , 1995; Nikkari et al , 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is most likely that the B19V DNA detected in whole blood represents viral DNA from B19V containing blood cells. Moreover, the presence of B19V DNA in peripheral blood cells has been shown previously by Kakurina et al (2015), while the presence of VP1 protein in synovial cells including lymphocytes, macrophages and neutrophils (e.g. cells present in the blood) was shown by Takahashi et al (1998).…”
Section: Discussionmentioning
confidence: 72%
“…The highest level of RA disease activity occurred in patients with active B19 infection 95. In conclusion, there is significant evidence that parvovirus B19 may play a role in the pathogenesis of RA.…”
Section: Autoimmune Diseases Associated With Parvovirus B19 Infectionmentioning
confidence: 80%
“…Association of B19 infection with RA has been demonstrated in several studies, while B19 specific cellular immune response in these patients was unknown (Takahashi et al, 1998;Murai et al, 1999;Stahl et al, 2000;Kozireva et al, 2008;Kakurina et al, 2015). Although B19 specific cellular immune responses have been investigated very poorly, the existing studies indicate the important role of these responses in the control of acute and persistent B19 infection (Fransilla et al, 2001;Tolfvenstam et al, 2001;Isa et al, 2005;Norbeck et al, 2005;Isa et al, 2006;Streitz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%